Framing Media: surya.co.id and jawapos.com on The Process of Face To Face Learning in Surabaya (Konstruksi Sosial Media Online pada Proses Pembelajaran Tatap Muka ) - Arsy, Azzukhrufina Nadia; Nurudin, Nurudin (ARISTO, 2022)
The Covid-19 pandemic is causing a variety of effects across sectors of life, including education. To reduce the transmission of Corona virus massively, the education process is conducted online. As online learning progressed there were many obstacles so that in the new normal era the Ministry of Education decided to return to face-to-face learning in schools for the yellow and green zones. Similarly, Surabaya has been proclaimed face to face learning although there are pro-cons because Surabaya is still the worst exposed area. This becomes a dilemma between the immediate application of face to face learning because online learning is no longer effective or prioritizes the health of students who are leading issues in online media coverage. This article discusses news framing on the issue of face-to-face learning from Surya.co.id and JawaPos.com media. This research is qualitative research with framing analysis of Robert Entman. The result of this study is that both media are strongly indicated framing in each news text shown through the elements of defining the problem to the solutions offered. In addition, both media also showed their impartiality by choosing speakers from the education elite only. Then each media emphasized problem solving for schools in Surabaya immediately prepare rules and scenarios of face-to-face learning in schools.